Utilization of Digital Technology in Enhancing Teachers' Pedagogical Competence - M. Munif; Johannes M. Galvis; Muh Habibulloh (Journal of Education and Learning Sciences, 2024)
This study aims to analyze the utilization of digital technology in enhancing teachers' pedagogical competence in madrasahs in Jombang Regency. The research employs a qualitative approach with a case study method. Data were collected through interviews, observations, and document analysis involving teachers, madrasah principals, and students. The findings indicate that digital technology has positively impacted teachers by enhancing their creativity and teaching effectiveness. The use of learning applications such as Google Classroom, Zoom, and Quizizz has helped teachers deliver lessons more interactively. Moreover, the integration of technology into learning has increased student engagement, particularly in discussions and group work. The study also reveals several challenges in implementing digital technology, such as limited infrastructure, lack of teacher training, and disparities in students' readiness. Some madrasahs still struggle with providing stable internet access and adequate learning devices. Additionally, resistance among some teachers due to limited digital skills and the time required to adjust teaching methods remains a challenge. To address these issues, strategies such as continuous teacher training, improvement of technological infrastructure, and the development of a more adaptive technology-based curriculum are necessary. By implementing these measures, the utilization of digital technology can be optimized to support the enhancement of teachers' pedagogical competence and the quality of learning in madrasahs in Jombang Regency.